Synthesis and photochromism of a novel amphiphilic diarylethene bearing two cholic acid groups. Issue 18 (4th May 2016) - Duan, Fang; Liu, Gang; Fan, Congbin; Pu, Shouzhi
Graphical abstract: Highlights: A novel amphiphilic diarylethene with two cholic acid groups has been synthesized by click reaction. The diarylethene exhibited notable photochromism, good fatigue-resistance, and excellent fluorescence switching property. The diarylethene exhibited high photoconversion ratio. Abstract: A novel amphiphilic diarylethene with two cholic acid groups, 1, 2-bis[2-methyl-5-[3-(1, 2, 3-triazole)methyl-5-cholic acid-3-thienyl]perfluorocyclopentene, has been successfully synthesized by click reaction for the first time and its photochromic, fluorescence, and electrochemistry properties were systematically investigated. This new compound showed good hydrophilia in methanol/water binary solution (v/v, 1:19). It exhibited photochromism with the notable color change from colorless to red and good fatigue-resistance by photoirradiation. Further study indicated that it also has excellent fluorescence switching property in methanol/water binary solution.